Control of immune cell signaling by the immuno-metabolite itaconate - Lang, Roland; Siddique, Md Nur A Alam (Frontiers in Immunology, 2024)
Immune cell activation triggers signaling cascades leading to transcriptional reprogramming, but also strongly impacts on the cell’s metabolic activity to provide energy and biomolecules for inflammatory and proliferative responses. Macrophages activated by microbial pathogen-associated molecular patterns and cytokines upregulate expression of the enzyme ACOD1 that generates the immune-metabolite itaconate by decarboxylation of the TCA cycle metabolite cis-aconitate. Itaconate has anti-microbial as well as immunomodulatory activities, which makes it attractive as endogenous effector metabolite fighting infection and restraining inflammation. Here, we first summarize the pathways and stimuli inducing ACOD1 expression in macrophages. The focus of the review then lies on the mechanisms by which itaconate, and its synthetic derivatives and endogenous isomers, modulate immune cell signaling and metabolic pathways. Multiple targets have been revealed, from inhibition of enzymes to the post-translational modification of many proteins at cysteine or lysine residues. The modulation of signaling proteins like STING, SYK, JAK1, RIPK3 and KEAP1, transcription regulators (e.g. Tet2, TFEB) and inflammasome components (NLRP3, GSDMD) provides a biochemical basis for the immune-regulatory effects of the ACOD1-itaconate pathway. While the field has intensely studied control of macrophages by itaconate in infection and inflammation models, neutrophils have now entered the scene as producers and cellular targets of itaconate. Furthermore, regulation of adaptive immune responses by endogenous itaconate, as well as by exogenously added itaconate and derivatives, can be mediated by direct and indirect effects on T cells and antigen-presenting cells, respectively. Taken together, research in ACOD1-itaconate to date has revealed its relevance in diverse immune cell signaling pathways, which now provides opportunities for potential therapeutic or preventive manipulation of host defense and inflammation.
CRIS-Team Scopus Importer:2024-03-29
Keywords: ACOD1; IRG1; itaconate; macrophages; metabolism; post-translational modification; signal transduction; transport

Divergent effects of itaconate isomers on Coxiella burnetii growth in macrophages and in axenic culture - Siddique, Md Nur A Alam; Kellermeier, Fabian; Ölke, Martha; Zhao, Mingming; Büssow, Konrad; Oefner, Peter J.; Lührmann, Anja; Dettmer, Katja; Lang, Roland (Frontiers in Immunology, 2024)
Aconitate decarboxylase-1 (ACOD1) is expressed by activated macrophages and generates itaconate that exerts anti-microbial and immunoregulatory effects. ACOD1-itaconate is essential for macrophage-mediated control of the intracellular pathogen Coxiella (C.) burnetii, which causes Q fever. Two isomers of itaconate, mesaconate and citraconate, have overlapping yet distinct activity on macrophage metabolism and inflammatory gene expression. Here, we found that all three isomers inhibited the growth of C. burnetii in axenic culture in ACCM-2 medium. However, only itaconate reduced C. burnetii replication efficiently in Acod1-/- macrophages. In contrast, addition of citraconate strongly increased C. burnetii replication in Acod1+/- macrophages, whereas mesaconate weakly enhanced bacterial burden in Acod1-/- macrophages. Analysis of intracellular isomers showed that exogenous citraconate and mesaconate inhibited the generation of itaconate by infected Acod1+/- macrophages. Uptake of added isomers into Acod1-/- macrophages was increased after infection for itaconate and mesaconate, but not for citraconate. Mesaconate, but not citraconate, competed with itaconate for uptake into macrophages. Taken together, inhibition of itaconate generation by macrophages and interference with the uptake of extracellular itaconate could be identified as potential mechanisms behind the divergent effects of citraconate and mesaconate on C. burnetii replication in macrophages or in axenic culture.
CRIS-Team Scopus Importer:2024-08-30
Keywords: ACOD1; citraconate; infection; IRG1; itaconate; mesaconate; transport; uptake

Itaconate mediates control of Coxiella burnetii infection in murine macrophages - Siddique, Md Nur A Alam; Kohl, Lisa; Berger, Raffaela; Schulze-Lührmann, Jan; Lührmann, Anja; Wilde, Katja Dettmer; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate